Modeling and optimization of cutting parameter during Wire-EDM of Inconel 718 using response surface - Kasim, Mohd Shahir; Raja, Izamshah; Joseph Sahaya Anand, T; Zakaria, Nor Fakhriah (2015)
This paper presents a study of the relationship between wire electrical discharge machine (WEDM) parameters and surface finish. The study analyzed the relationship between cutting parameter as variable input and surface roughness as output. To optimize the surface roughness which were measured both in horizontal and vertical direction, a Box Behnken of response surface design (RSM) with three process parameter, voltage, current and feed rate is used. Analysis of variance (ANOVA) was used to identify the identified the parameters affecting the machined surface finish. With the result of P-Value and F-Value, machining current is known as the most contributing factor, followed by feed rate and machining voltage. The direction of measurement was found not to be significant. The linear prediction models were developed with average error of 3.67% and 1.74% horizontal and vertical surfaced roughness measurement direction respectively. The result of the validation also shows a good agreement with predicted values. It is beneficial as to assist machinist in improving the quality of the WEDM surface.